History and Tropology The Rise and Fall of Metaphor. - Ankersmit, F. R. (University of California Press, 2020)
""The chief business of twentieth-century philosophy"" is ""to reckon with twentieth-century history,"" claimed R. G. Collingwood. In this remarkable collection of essays, Frank Ankersmit demonstrates the prescience of that remark and goes a long way toward meeting its challenge. Responding to the work of Hayden White, Arthur Danto, and Hans-Georg Gadamer, he examines such issues as the difference between historical representation and artistic expression, the.